Bail-in in action - David Marqués Ibá\~nez; Gianluca Santilli; Giulia Scardozzi (European Central Bank (ECB), 2024)
In the aftermath of the European sovereign debt crisis, the question of who should bear the burden of banking crises has been a cornerstone of the new supervisory framework in Europe. We evaluate the bail-in regulation (BRRD) for bank bond holdings using a proprietary database covering holdings of all euro-denominated securities. We focus on hard-to-value bailinable bank bonds and show that banks increased their holdings of bailinable bank bonds while households and non-financial corporations reduced their holdings of bailinable bonds issued by riskier banks.
Keywords: G21; G28; 330; Bail-in; Bond holdings; Bond allocation